Efficacy of fresh packed red blood transfusion in organophosphate poisoning. Issue 11 (March 2017) - Bao, Hang-xing; Tong, Pei-jian; Li, Cai-xia; Du, Jing; Chen, Bing-yu; Huang, Zhi-hui; Wang, Ying
Abstract : Abstract: The mortality rate caused by organophosphate (OP) poisoning is still high, even the standard treatment such as atropine and oxime improves a lot. To search for alternative therapies, this study was aimed to investigate the effects of packed red blood cell (RBC) transfusion in acute OP poisoning, and compare the therapeutic effects of RBCs at different storage times. Patients diagnosed with OP poisoning were included in this prospective study. Fresh RBCs (packed RBCs stored less than 10 days) and longer-storage RBCs (stored more than 10 days but less than 35 days) were randomly transfused or not into OP poisoning patients. Cholinesterase (ChE) levels in blood, atropine usage and durations, pralidoxime durations were measured. We found that both fresh and longer-storage RBCs (200–400 mL) significantly increased blood ChE levels 6 hours after transfusion, shortened the duration for ChE recovery and length of hospital stay, and reduced the usage of atropine and pralidoxime. In addition, fresh RBCs demonstrated stronger therapeutic effects than longer-storage RBCs. Packed RBCs might be an alternative approach in patients with OP poisoning, especially during early stages.